Tathawwur al-Tafsīr Malāyū: Dirāsah Tahlīliyyah fī Tajdīd al-Tafsīr al-Furqān Li Ahmad Hasan - Ali Muhtadin; Ajib Raghib Darsie (Center for Research and Development of Religious Literature and Heritage, 2024)
This research delves into the study of a Qur'anic exegesis that marks a milestone in the renewal of interpretive traditions in early 20th-century Indonesia. Through a qualitative descriptive-analytical approach, this study examines A. Hassan's innovative methodology that integrates the concise and analytical methods of interpretation, with an emphasis on social context and rationality. The main focus of the research is to analyze the uniqueness of A. Hassan's approach in interpreting the Qur'an and to explore his role as a reformer in the Malay-Nusantara exegetical tradition. A literature study was used for data collection, while Fazlur Rahman's theory of modern Islamization was applied to understand the responsiveness to contemporary societal issues. This study also investigates the impact of using the Indonesian language and Latin script, which significantly increased the accessibility of Qur'anic interpretation in Indonesia. Furthermore, the study examines the work's contribution in stimulating the renewal of religious thought and fostering the spirit among Indonesian Muslims. The research findings reveal that is not merely a theological exegetical work, but also functions as a crucial agent of social and intellectual change in the Islamic reform movement in Indonesia at the beginning of the 20th century. This work bridges the gap between classical traditions and the demands of modernity, paving the way for a more contextual and relevant interpretation of the Qur'an for Indonesian society.